Cortical ionotropic glutamate receptor antagonism protects against methamphetamine-induced striatal neurotoxicity - Gross, Noah B. (2011)
Binge administration of the psychostimulant drug, methamphetamine (mAMPH), produces long-lasting structural and functional abnormalities in the striatum. mAMPH binges produce non-exocytotic release of dopamine (DA), and mAMPH-induced activation of excitatory afferent inputs to cortex and striatum is evidenced by elevated extracellular glutamate (GLU) in both regions. The mAMPH-induced increases in DA and GLU neurotransmission are thought to combine to injure striatal DA nerve terminals of mAMPH-exposed brains. Systemic pretreatment with either competitive or noncompetitive N-methyl-D-aspartic acid (NMDA) antagonists protects against mAMPH-induced striatal DA terminal damage, but the locus of these antagonists’ effects has not been determined. Here, we applied either the NMDA receptor antagonist, (DL)-amino-5-phosphonovaleric acid (AP5), or the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor antagonist, dinitroquinoxaline-2,3-dione (DNQX), directly to the dura mater over frontoparietal cortex to assess their effects on mAMPH-induced cortical and striatal immediate-early gene (c-fos) expression. In a separate experiment we applied AP5 or DNQX epidurally in the same cortical location of rats during a binge regimen of mAMPH, and assessed mAMPH-induced striatal dopamine transporter (DAT) depletions one week later. Our results indicate that both ionotropic glutamate receptor antagonists reduced the mAMPH-induced Fos expression in cerebral cortex regions near the site of epidural application and reduced Fos immunoreactivity in striatal regions innervated by the affected cortical regions. Also, epidural application of the same concentration of either antagonist during a binge mAMPH regimen blunted the mAMPH-induced striatal DAT depletions with a topography similar to its effects on Fos expression. These findings demonstrate that mAMPH-induced dopaminergic injury depends upon cortical NMDA and AMPA receptor activation and suggest the involvement of the corticostriatal projections in mAMPH neurotoxicity.